Encapsulation of the HSP-90 Chaperone Inhibitor 17-AAG in Stable Liposome Allow Increasing the Therapeutic Index as Assessed, in vitro, on Leishmania (L) amazonensis Amastigotes-Hosted in Mouse CBA Macrophages - Petersen, Antonio Luis de Oliveira Almeida; Campos, Thiers A.; Dantas, Diana Angélica dos Santos; Rebouças, Juliana de Souza; da Silva, Juliana Cruz; de Menezes, Juliana P. B.; Formiga, Fábio R.; de Melo, Janaina V.; Machado, Giovanna; Veras, Patrícia S. T. (Frontiers in Cellular and Infection Microbiology, 2018)
The current long-term treatment for leishmaniasis causes severe side effects and resistance in some cases. An evaluation of the anti-leishmanial potential of an HSP90-inhibitor, 17-allylamino-17-demethoxygeldanamycin (17-AAG), demonstrated its potent effect against Leishmania spp. in vitro and in vivo. We have previously shown that 17-AAG can kill L. amazonensis promastigotes with an IC50 of 65 nM and intracellular amastigote at concentrations as low as 125 nM. As this compound presents low solubility and high toxicity in human clinical trials, we prepared an inclusion complex containing hydroxypropyl-β-cyclodextrin and 17-AAG (17-AAG:HPβCD) to improve its solubility. This complex was characterized by scanning electron microscopy, and X-ray diffraction. Liposomes-containing 17-AAG:HPβCD was prepared and evaluated for encapsulation efficiency (EE%), particle size, polydispersity index (PDI), pH and zeta potential, before and after accelerated and long-term stability testing. An evaluation of leishmanicidal activity against promastigotes and intracellular amastigotes of L. amazonensis was also performed. The characterization techniques utilized confirmed the formation of the inclusion complex, HPβCD:17-AAG, with a resulting 33-fold-enhancement in compound water solubility. Stability studies revealed that 17-AAG:HPβCD-loaded liposomes were smaller than 200 nm, with 99% EE. Stability testing detected no alterations in PDI that was 0.295, pH 7.63 and zeta potential +22.6, suggesting liposome stability and suitability for evaluating leishmanicidal activity. Nanoformulations killed L. amazonensis promastigotes at very low concentrations, with an IC50 value of 0.006 nM for 17-AAG:HPβCD-loaded liposomes, while unloaded control liposomes presented toxicity at concentrations 79x higher. Treatment of infected macrophages with 0.006 nM of 17-AAG:HPβCD or 17-AAG:HPβCD-loaded liposomes resulted in almost complete parasite clearance inside macrophages after 48 h. Our results showed that nanotechnology and drug delivery systems could be used to increase the antileishmanial efficacy and potency of 17-AAG in vitro, while also resulting in reduced toxicity that indicates these formulations may represent a potential therapeutic strategy against leishmaniasis.